MEASURING AND PROFILING STUDENTS' CRITICAL THINKING SKILLS ON CHEMICAL EQUILIBRIUM USING THE RASCH MODEL - Mardhiya, Julia; Sari, Dwy Puspita (UNESA Journal of Chemical Education, 2025)
This research focused on measuring students' critical thinking skills in the topic of chemical equilibrium. The instrument used is an essay test consisting of 8 questions. Data collection took place from March to April 2024. The sample size was 80 students. Data were analyzed using the Rasch Model with Winsteps 5.6.0. The instrument underwent testing for unidimensional, validity (item fit), reliability, item difficulty level (item measure), and individual ability level (person measure). The analysis showed that the instrument had a person reliability of 0.64 and item reliability of 0.96. The interaction between person and items is displayed on the Wright Map and Scalogram. The analysis of person and items provided significant information about the participants' abilities and the difficulty levels of the tested questions. A total of 4 respondents were identified as misfit according to the model. The identification of person misfit also plays a role in understanding patterns of responses that do not align with the model. The findings of this study can serve as a reflection for both students and lecturers regarding students' critical thinking skills.